Detrimental role for CD4+ T lymphocytes in murine diffuse peritonitis due to inhibition of local bacterial elimination. Issue 2 (26th October 2007) - Busse, M; Traeger, T; Pötschke, C; Billing, A; Dummer, A; Friebe, E; Kiank, C; Grunwald, U; Jack, R S; Schütt, C; Heidecke, C-D; Maier, S; et al.
Abstract : Background: Abdominal sepsis due to intestinal leakage of endogenous gut bacteria is a life-threatening condition. In healthy individuals, T lymphocytes have essential functions in balancing the immune response to the commensal gut flora. Aim: To determine how T lymphocytes shape the process of diffuse faecal peritonitis. Methods: In colon ascendens stent peritonitis (CASP), a clinically relevant mouse model of diffuse peritonitis, the kinetics of systemic T cell activation were investigated by assessment of activation markers. CD4 + T cells were then depleted with monoclonal antibodies, and survival, bacterial dissemination and cytokine concentrations were measured. T cell receptor signalling was blocked with tacrolimus. Results: In diffuse peritonitis, CD4 + T cells, both Foxp3 − and Foxp3 +, became systemically involved within hours and upregulated CTLA-4 and other activation markers. Depletion of the CD4 + T cells enhanced local bacterial clearance from the peritoneal cavity, reduced bacterial dissemination and improved survival. This was accompanied by increased immigration of granulocytes and macrophages into the peritoneum, indicating that CD4 + T cells inhibit the local innate immune response. Blockade of T cell receptor (TCR) signalling by tacrolimus did not influence the survival in this peritonitis model, showing that the inhibitory effects of the CD4 + T lymphocytes were independent of TCR-mediated antigen recognition. Conclusion: In diffuse peritonitis caused by commensal gut bacteria the CD4 + T lymphocytes exert a net negative effect on the local anti-bacterial defence, and thereby contribute to bacterial dissemination and poor outcome.